2021
DOI: 10.3389/fmed.2021.779019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neuromuscular Electrical Stimulation After Total Knee Arthroplasty: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: This systematic review and meta-analysis aimed to evaluate the effect of neuromuscular electrical stimulation (NMES) on quadriceps muscle strength, pain, and function outcomes following total knee arthroplasty (TKA).Methods: PubMed/Medline, Embase, Web of Science, CENTRAL, Scopus, PsycINFO, PEDro, CINAHL, CNKI, and Wanfang were systematically searched for randomized controlled trials (RCTs) from their inception to 18 June 2021.Results: Nine RCTs that involving 691 patients were included in the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(175 reference statements)
0
3
0
Order By: Relevance
“…NMES has been used as an alternative to exercise in patients with decreased physical activity, such as in post stroke patients [ 10 ]. Furthermore, a systematic review reported that NMES effectively increased lower limb muscle strength after orthopedic surgery [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…NMES has been used as an alternative to exercise in patients with decreased physical activity, such as in post stroke patients [ 10 ]. Furthermore, a systematic review reported that NMES effectively increased lower limb muscle strength after orthopedic surgery [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) is highly effective at relieving joint disease-induced pain and improving joint functions (1)(2)(3). However, blood loss during TKA is high, and is estimated to exceed 1,000 ml with 10-38% of patients requiring blood transfusion (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Several modalities and techniques, such as hydrotherapy [ 7 ], cryotherapy [ 8 ], neuromuscular electrical stimulation [ 9 ], and continuous passive motion therapy [ 10 ]. However, while some showed positive effects [ 9 , 11 ], the clinical benefits of others remain uncertain [ 4 , 12 , 13 ], and there remains an unmet need for innovative post-TKA rehabilitation approaches that can provide significant clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%